Analisis Sistem Pengendalian Intern untuk Mendukung Akuntabilitas Keuangan, Tata Kelola dan Teknologi Pemerintahan Daerah - Apria Yosa Saputri; Nedi Hendri; Ana Septiani (Universitas Muhammadiyah Metro, 2026)
This study aims to analyze the implementation of the Integrated Government Internal Control System (SPIP-T) in supporting financial accountability, governance, and the use of information technology within the Inspectorate of Metro City. The research was conducted qualitatively using a descriptive method through interviews, documentation, and direct observation. The results show that SPIP-T has contributed to improving the effectiveness of supervision, work process efficiency, and financial reporting. However, several weaknesses were identified, such as budget planning that is not risk-based, misaligned budget allocations for supervision, and human resources whose competencies do not meet the required standards.SPIP-T was also found to be suboptimal in supporting the use of information technology. The study recommends strengthening human resource competencies, utilizing digital technology, and integrating risk-based supervision systems.